The Outcome of Kidney Transplant Recipients Who Had Combined ABO Incompatibility and Preformed Antibody Against Donor HLA Antigen. (July 2018) - Kim, Mihyeong; Moon, Insung; Jun, Kangwoong; Hwang, Jeongkye; Kim, Sangdong; Park, Suncheol; Kim, Jiil
Abstract : Introduction: Advances in desensitization therapy and immunosuppressants made kidney transplantation possible in a recipient who had incompatible blood type with donor or preformed antibody against donor human leukocyte antigen (HLA). However, we can`t guarantee the outcome who has these immunologic risk factors together. We aimed this study to investigate safety and outcome of these highly sensitized kidney transplantation. Methods: Between May 2009 and May 2016, we reviewed medical records of patients who undertaken kidney transplantation in Seoul St. Mary`s hospital. We included patient who is ABO-incompatible and in the same time matched following conditions; (1) positive result in crossmatch test and/or (2) donor specific antibody with mean fluorescent intensity (MFI) over 5000 measured by Luminex single antigen assay. Results: Twelve (54.5%) recipients were female and among them, nine were married. Nine donors gave a kidney to their spouse, four cases were husband to wife donation. Eight (36.3%) were their 2nd transplantation in this time. The mean of HLA mismatch number was 3.4 and all patients were positive in crossmatch test; 2 in T-cell CDC, 3 in B-cell CDC, 9 in T-cell flowcytometry and 14 in B-cell flowcytometry. Seventeen (77.2%) had panel reactive antibody test positivity over 50%. Anti-ABO antibody titer was ⩽ 1:64 in sixteen patients (72.7%). Average seven sessions of plasmapheresis were done before transplantation. There were two cases of delayed graft function, however, primary failure was not occurred. A patient was expired with functioning graft three days after transplantation due to Stanford type A aortic dissection. There were 3 cases of graft failure at 1916, 626, 1162 days after transplantation, respectively. All graft failure was induced by acute rejection, one was antibody-mediated, other one was T-cell mediated and the left was antibody- and cell-mediated together. Most common postoperative complication was infection; fourteen patients (63%) got bacterial infection and eleven (49%) were involved viral infection. Rejection was occurred in ten patients (45.4%), total nineteen events. We analyzed the graft survival according to presence of rejection episode, the result was inferior in patients who had rejection episode, but there was not statistical significance (p=0.102) We compared graft survival of presented patients with standard ABOi KT patients (n=88) and sensitized to donor HLA antigen patients (n=51) performed same period in our institute and there was no statistical significance (p=0.788). Conclusions: A recipient who had combined immunologic risk of blood type incompatibility and preformed antibody against donor HLA antigen presented comparable outcome to a patient who had one of these risk factors. However, they were frequently involved infectious condition or rejection, we need to pay special attention during long-term follow-up.